Supporting Tables and Figures from Cool-edge populations of the kelp Ecklonia radiata under global ocean change scenarios: strong sensitivity to ocean warming but little effect of ocean acidification ... - Britton, Damon; Layton, Cayne; Mundy, Craig N.; Brewer, Elizabeth A.; Gaitán-Espitia, Juan Diego; Beardall, John; Raven, John A.; Hurd, Catriona L. (The Royal Society, 2023)
Additional tables and figures not included in main article. ...